1965
DOI: 10.1111/j.1476-5381.1965.tb01628.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ascorbic Acid on Histamine Metabolism in Guinea‐pigs

Abstract: The influence of ascorbic acid on anaphylaxis has always been a subject of controversy. For example, Cohen (1939) and van Niekerk (1937) found that ascorbic acid did not protect guinea-pigs from anaphylactic shock, whereas Hochwald (1935) obtained protection with large doses. Further, Giroud, Giroud, Ratsimamanga & Rabinowicz (1936) found that, by using daily doses of ascorbic acid during the period of antibody formation, the degree of sensitization was increased, whilst Zolog (1924) claimed that it was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
1

Year Published

1966
1966
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…Rosa & Parenti (1950) used the vitamin in bronchial asthma and urticaria with some success, but Naranjo (1952) and Herxheimer (1955) obtained no protection against anaphylaxis in experimental animals. Hochwald (1935), van Niekerk (1937), Aron (1948) and Dawson & West (1965a) all showed a shortterm protective action of ascorbic acid against anaphylaxis in guinea-pigs. These protective effects have usually been obtained in guinea-pig and man in allergic conditions where contraction of the bronchial smooth muscle is of prime importance and it is suggested that the protection is due to a direct action of the vitamin on the smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosa & Parenti (1950) used the vitamin in bronchial asthma and urticaria with some success, but Naranjo (1952) and Herxheimer (1955) obtained no protection against anaphylaxis in experimental animals. Hochwald (1935), van Niekerk (1937), Aron (1948) and Dawson & West (1965a) all showed a shortterm protective action of ascorbic acid against anaphylaxis in guinea-pigs. These protective effects have usually been obtained in guinea-pig and man in allergic conditions where contraction of the bronchial smooth muscle is of prime importance and it is suggested that the protection is due to a direct action of the vitamin on the smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid may have a synergistic effect when administered with antihistamines against allergic phenomena (Dawson & West, 1965a) …”
Section: Discussionmentioning
confidence: 99%
“…High doses of ascorbic acid protect sensitized guinea-pigs maintained on a normal diet against the effects of antigen aerosols ' (Dawson & West, 1965a;Guirgis, 1965). Actively sensitized scorbutic guinea-pigs are less sensitive to antigen aerosols than guinea-pigs maintained on normal diets (Dawson & West, 1965a).…”
Section: Introductionmentioning
confidence: 99%
“…The role of ascorbic acid (vitamin C) in asthma has long been argued, early as 1803 Reisseissen suggested that vitamin C prevents the wheezing observed in patients with diseases scurvy [4]. More recently, animal studies have shown that ascorbic acid may prevent anaphylaxis and other allergic phenomena [5,6]. In guinea pigs, ascorbic acid has been shown to reduce the airway obstruction prompted by 5-hydroxytryptamine, bradykinin, and histamine [7].…”
Section: Introductionmentioning
confidence: 99%